Death in the midst of life perspectives on death from Christianity and depth psychology - Bregman, Lucy (Grand Rapids, MI Baker, 1992)
Includes bibliographic references and index.
Keywords: Death -- religious aspects -- Christianity; Death -- psychological aspects; Psychoanalysis and religion; Death -- biblical teaching; Bible. N.T. -- criticism, interpretation, etc